2021
DOI: 10.1136/emermed-2020-210030
|View full text |Cite
|
Sign up to set email alerts
|

Higher clinical acuity and 7-day hospital mortality in non-COVID-19 acute medical admissions: prospective observational study

Abstract: ObjectivesTo understand the effect of COVID-19 lockdown measures on severity of illness and mortality in non-COVID-19 acute medical admissions.DesignA prospective observational study.Setting3 large acute medical receiving units in NHS Lothian, Scotland.ParticipantsNon-COVID-19 acute admissions (n=1682) were examined over the first 31 days after the implementation of the COVID-19 lockdown policy in the UK on 23 March 2019. Patients admitted over a matched interval in the previous 5 years were used as a comparat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Additionally, during COVID-19 surges, many elective admissions were canceled, resulting in higher acuity patient populations. [20] Limitations of this study include use of NHSN-reported HAI events. Variations in surveillance and reporting may affect NHSN HAI data, especially when infection prevention activities are constrained.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, during COVID-19 surges, many elective admissions were canceled, resulting in higher acuity patient populations. [20] Limitations of this study include use of NHSN-reported HAI events. Variations in surveillance and reporting may affect NHSN HAI data, especially when infection prevention activities are constrained.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Historically, in the healthcare system, this disproportionate strain is noticed in both the emergency room and the intensive care unit with increased adverse patient outcomes. [7][8][9][10] This is quite tangible given the current Coronavirus disease 2019 (COVID- 19) pandemic, which has resulted in over 5 million deaths worldwide and has become a MCD of biological origin. 3,[6][7][8][9][10][11][12] Highlighted during the COVID-19 pandemic, elderly populations are among the most vulnerable populations impacted by MCDs due to their decreased mobility and comorbid conditions.…”
mentioning
confidence: 99%
“…[7][8][9][10] This is quite tangible given the current Coronavirus disease 2019 (COVID- 19) pandemic, which has resulted in over 5 million deaths worldwide and has become a MCD of biological origin. 3,[6][7][8][9][10][11][12] Highlighted during the COVID-19 pandemic, elderly populations are among the most vulnerable populations impacted by MCDs due to their decreased mobility and comorbid conditions. [13][14][15][16] Furthermore, individuals with disabilities and/or denoted to be in a high-risk group delay their presentation to seek medical care, even in the presence of worsening conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations